2018
DOI: 10.18203/issn.2455-4510.intjresorthop20182473
|View full text |Cite
|
Sign up to set email alerts
|

Propellar flap: safe, reliable option for coverage of exposed tendo achilles

Abstract: <p class="abstract"><strong>Background:</strong> Stable skin cover over exposed tendo achilles is absolutely essential for proper healing and recovery of tendo achilles function. Exposed tendo achilles can be a result of open injuries, repair of closed TArupture, complications after repair like suture dehiscence, skin necrosis, infection, delayed exposure and recurrent rupture. Various methods have been described for coverage of repaired tendo achilles like distally based skin flaps, advancem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Other studies 6 , 15 , recommended the use of distal posterior tibial artery adipofascial flap covered with STSG for reconstruction of soft tissue defects of the AT as it gives good functional outcome with minimal donor site morbidity and satisfactory cosmetic results even in female patients. Jammula et al 9 preferred to use island propeller flaps to cover the exposed AT and reported excellent functional results with stable covering in all except one patient that had flap failure due to impaired venous return. In another study, Gopalakrishnan et al 5 reconstructed soft tissue defects of the Achilles region with fasciocutaneous flaps (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies 6 , 15 , recommended the use of distal posterior tibial artery adipofascial flap covered with STSG for reconstruction of soft tissue defects of the AT as it gives good functional outcome with minimal donor site morbidity and satisfactory cosmetic results even in female patients. Jammula et al 9 preferred to use island propeller flaps to cover the exposed AT and reported excellent functional results with stable covering in all except one patient that had flap failure due to impaired venous return. In another study, Gopalakrishnan et al 5 reconstructed soft tissue defects of the Achilles region with fasciocutaneous flaps (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are many reconstructive modalities including, local fasciocutaneous or adipofascial flaps 4 , 6 , 7 , muscle flaps 8 , propeller flaps 9 , and free flaps 10 , 11 , there is still controversy regarding the optimal treatment. With the remarkable development of reconstructive microsurgery, recent studies have outlined the use of free flaps as the first choice in the management of such defects 12 .…”
Section: Introductionmentioning
confidence: 99%
“…4 Various flaps have been described in literature for cover over tendo Achilles like distally based skin flaps, advancement flap, free tissue transfers and islanded flaps. [5][6][7] The use of free flaps has improved the ability to cover soft tissue defects. However, the flap bulk, the need for secondary procedures, and the risk of vascular failure are considerable drawbacks.…”
mentioning
confidence: 99%